Considering Space : A Critical Concept for the Social Sciences. - Bartmanski, Dominik. (The Refiguration of Space Series, 2023)
Showing how society can and should be perceived as spatial, this book demonstrates what has changed in the perception of space within the social sciences and how useful - indeed indispensable - concepts of space and spatial concepts remain today.